2020
DOI: 10.7150/ijms.39622
|View full text |Cite
|
Sign up to set email alerts
|

Water extract of tendril of Cucurbita Moschata Duch. suppresses RANKL-induced osteoclastogenesis by down-regulating p38 and ERK signaling

Abstract: Background: Pumpkin (Curcubita sp.) is a natural product that is commonly used in folk medicine. However, the inhibitory effect and molecular mechanisms of tendril of Cucurbita Moschata Duch. (TCMD) on osteoclast differentiation have yet to be clearly elucidated. Thus, the present study aimed to investigate the effect and underlying mechanism of water extract of TCMD on osteoclast differentiation. Methods: Bone marrow-derived macrophages (BMDMs), osteoclast precursors, were cultured with macrophage colony stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A large body of evidence has been collected to show the potential of plant derivatives for the prevention and treatment of bone lesions [ 12 , 13 , 14 ]. Despite various discrepancies in the literature, there is agreement in attributing the positive effects of plant extracts, including those of the pumpkin tendrils, on the bone repair process, to antioxidant and anti-inflammatory action, and to the ability to increase angiogenesis and cell proliferation and differentiation [ 13 , 15 , 16 , 17 ]. Consistently with those observations, the few characteristics of pumpkin leaf extracts known prior to our study suggested that it would be reasonable to investigate their effects on bone cells.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of evidence has been collected to show the potential of plant derivatives for the prevention and treatment of bone lesions [ 12 , 13 , 14 ]. Despite various discrepancies in the literature, there is agreement in attributing the positive effects of plant extracts, including those of the pumpkin tendrils, on the bone repair process, to antioxidant and anti-inflammatory action, and to the ability to increase angiogenesis and cell proliferation and differentiation [ 13 , 15 , 16 , 17 ]. Consistently with those observations, the few characteristics of pumpkin leaf extracts known prior to our study suggested that it would be reasonable to investigate their effects on bone cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that a water extract of pumpkin tendril suppresses RANKL-induced osteoclast differentiation and bone resorption by suppressing RANKL-mediated p38 and ERK phosphorylation [17]. In addition, water extract of pumpkin tendril treatment decreased the expression of osteoclast-related genes such as NFATc1, TRAP, Cathepsin K and TRAP [17]. In our study, new compounds isolated from a water extract of pumpkin tendril showed different levels of inhibitory effects at the same concentration.…”
Section: Inhibition Of Rankl-induced Osteoclast Differentiation In Bone Marrow Derived Macrophages (Bmdms) By the Isolated Compoundsmentioning
confidence: 46%
“…Pumpkin tendril has also been found to inhibit inflammation, with rutin being identified as an anti-inflammatory compound in this material [16]. Recently, we reported that the water extract of pumpkin tendrils suppressed RANKL-induced osteoclast differentiation via downregulation of p38 and extracellular-signal-regulated kinase (ERK) [17]. Nevertheless, the results of our series of studies on pumpkin tendril suggested the presence of other unidentified bioactive compounds.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The femur and tibia of C57BL/6 mice (age:7±1weeks, weight:22 ± 2 g, purchased from Kawensi, Changzhou, China) were utilized to harvest total bone marrow cells [ 22 ]. These cells were subsequently cultured in culture medium supplemented with 10% FBS, 1% penicillin and streptomycin, and 30 ng/ml M-CSF at 37 °C and 5% CO 2 [ 23 ]. Osteoclast induction was performed when cells reached 90%–100% confluence.…”
Section: Methodsmentioning
confidence: 99%